The association between the MIND diet and cognitive health in middle-aged and older adults: A systematic review - Jenny Hiu Wai Tse; Queenie Pui Sze Law; Jenny Tsun Yee Tsang; Lorna Kwai Ping Suen; Stefanos Tyrovolas; Rick Yiu Cho Kwan (The Journal of Nutrition, Health and Aging)
Background: Cognitive decline, a natural aspect of aging, is linked to negative outcomes like increased mortality and social isolation. The Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet, blending the Mediterranean diet and the Dietary Approaches to Stop Hypertension (DASH) diet elements, aims to slow cognitive decline and reduce dementia risk. Secondary analyses of population studies and randomized controlled trials (RCTs) show mixed results on the MIND diet's effectiveness in improving cognitive health. Existing reviews have explored the MIND diet's impact on cognitive health, though their focus can be broad or narrow. Our review offers an updated perspective by specifically targeting dementia risk and clinical cognitive function, integrating new studies for enhanced insights into clinical practice and research. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 and the Synthesis Without Meta-analysis (SWiM) guidelines and was registered in PROSPERO (CRD42023391972). We included quantitative studies on middle-aged and older adults (mean age >40 years) examining MIND diet adherence and cognitive health, excluding non-original research. A systematic search was conducted in five databases from March 2023 to March 2024 using relevant search terms. Data were extracted and assessed for bias by multiple reviewers using Joanna Briggs Institute (JBI) tools. Heterogeneous data were synthesized using SWiM guidelines, focusing on cognitive function outcomes, with results presented in tables and figures. Results: The search over five databases identified 898 articles, with 26 meeting the inclusion criteria. A hand search added 13 more, totaling 39 articles from 14 countries, including cohorts, cross-sectional, RCTs, and case-control studies. Most studies were conducted in the United States of America (USA), published between 2015 and 2024. Participant numbers ranged from 37 to 120,661, with follow-ups from 3 months to 24 years. Some studies explored more than one correlation. Of the studies, 14 out of 19 articles explored MIND diet adherence and global cognitive function, showing positive results. 10 out of 11 studies investigated MIND diet adherence and dementia/Alzheimer’s risk, showing positive associations. 16 out of 18 articles examined the MIND diet's effect on domain-specific cognitive functions, with favorable outcomes. Discussion: This systematic review reveals the significant promise of the MIND diet in enhancing cognitive health, specifically in global cognition, memory, and executive function. While observational studies strongly advocate for its inclusion in clinical guidelines to prevent and manage Alzheimer's disease (AD) and dementia, results from RCTs are mixed, suggesting further investigation is needed. The use of PRISMA and SWiM guidelines ensures robust and transparent findings, categorizing cognitive outcomes into critical areas for a holistic insight. Despite the effectiveness of alternative methods, such as MIND diet questionnaires, for adherence assessment apart from FFQ, variability in study populations, interventions, and scoring methods complicates pinpointing an optimal MIND score. This underscores the importance of standardized methodologies to refine dietary recommendations and consolidate the diet's cognitive health benefits across various populations.